KEBERHASILAN BELAJAR SISWA SMA PADA MATERI AJAR LAJU REAKSI MELALUI PEMBELAJARAN BERBASIS MASALAH MENGGUNAKAN WEBLOG - Eko Martin Sinaga; Albinus Silalahi (Universitas Negeri Medan, 2020)
This study aims to show: (1) the difference between the student learning outcomes taught by the PBL model using weblog media (PBL-WM) and taught by the same learning model but not using the media (PBL); (2) the correlation between student learning motivation and PBL-WM improvement; (3) differences in student learning motivation based on PBL-WM and PBL. The sample studied was class XI student of SMA Negeri 1 Percut Sei Tuan in the academic year 2019/2020 on the reaction rate teaching in 2013 curriculum. The instrument that used by test (learning outcome) and non-test (motivation). The results showed the average increase in PBL-WM was 74.7; while the average increase in PBL was 62,658. The average student motivation based on PBL-WM was 85.92; while the average student motivation based on PBL was 78.45. The statistical analysis results of SPSS 22.0 at α=5% can be stated that (1) PBL-WM was higher than PBL; (2) there was a significant correlation between student learning motivation and increase in PBL-WM , with a correlation coefficient of 0.925 and the contribution of learning motivation to increase PBL-WM of 85.5% while 14.5% was influenced by other factors; (3) student motivation based on PBL-WM was higher than PBL.